Impact of mobile payment applications and transfers on business - Opati, Thaisaiyi Zephania, 1979-; Gachukia, Martin Kang'ethe, 1979- (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book explores the impact of mobile money transfer and its impact on social, corporate, micro, and macro policies concerning the aggregated economy and individual households as a whole within an economy"--